Concept Mapping as a Successful Tool of Teaching-Learning and Evaluation in Primary Grades - GUPTA, RATNA (THE PRIMARY TEACHER, 2015)
There are various methods of teaching as lecture method, seminar method, discussion method, learning by doing, play way method, etc. One of these methods is concept mapping method which is comparatively less heard. Concept mapping is a graphical tool for organising and representing knowledge. It includes concepts, usually enclosed in circles or boxes of some type and relationship between concepts is indicated by a connecting line. Words written on the connecting line referred to as linking words or linking phrases, specify the relationship between the two concepts. Is concept mapping a successful tool of teaching learning and evaluation in primary grades? This research paper inquires about it.